2021
DOI: 10.1093/jas/skab019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of models for missing pedigree in single-step genomic prediction

Abstract: Pedigree information is often missing for some animals in a breeding program. Unknown-parent groups (UPGs) are assigned to the missing parents to avoid biased genetic evaluations. Although the use of UPGs is well-established for the pedigree model, it is unclear how UPGs are integrated into the inverse of the unified relationship matrix (H-inverse) required for single-step genomic best linear unbiased prediction. A generalization of the UPG model is the metafounder (MF) model. The objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
5
23
2
Order By: Relevance
“…Our results indicate that when the QP transformation is used, GT_H is as practical an alternative as GT_A 22 . This result is different from the results from other studies [16,18], where GT_A 22 , which was called altered H-inverse, had better predictive abilities than the full QP model GT_H.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results indicate that when the QP transformation is used, GT_H is as practical an alternative as GT_A 22 . This result is different from the results from other studies [16,18], where GT_A 22 , which was called altered H-inverse, had better predictive abilities than the full QP model GT_H.…”
Section: Resultscontrasting
confidence: 99%
“…Thus, the results indicate that, both in terms of bias and reliability, the MF model was slightly better than the other models. This conclusion is similar to that of other studies where the use of the MF model improved the single-step evaluations, e.g., [17,18]. Similarly, the MF approach seems to give better b 1 and R 2 values than the UPG model for the animal model without genomic information.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this method, breeding values of animals with missing pedigrees are adjusted according to the fraction of genes originating from each unknown parent group [34]. The accurate estimates of unknown parent groups rely on having many observations [35,36]. In this research study, the small size of the dataset limited our ability to investigate the differences in the accuracy of predictions with and without unknown parent groups in the model.…”
Section: Resultsmentioning
confidence: 99%
“…Those authors used about 860k genotyped animals and demonstrated that old phenotypic records (i.e., before 2000) can be removed without reducing prediction accuracy of young selection candidates. Moreover, they concluded that the best way to consider UPG in ssGBLUP is to include them in both A and the relationship matrix among genotyped animals (A 22 ), as also described by Tsuruta et al (2019) and Masuda et al (2021). Another advantage of ssGBLUP is the consideration of genomic preselection (Masuda et al, 2018), that is, animals selected based on their GEBV before they have phenotypes available (Patry and Ducrocq, 2011;Jibrila et al, 2020).…”
Section: Introductionmentioning
confidence: 99%